Astronomical spectroscopy on m-type red giant stars / Mohd Hafiz bin Mohd Saadon - Mohd Saadon, Mohd Hafiz (2014)
Red giant phase is one of the phases in stellar evolutionary tracks. The main focus of the study is to explore the late M-type red giant stars by using astronomical spectroscopy technique. Astronomical spectroscopy method is used in order to understand the chemical abundances and the pattern and characteristics of the spectrum of this type of stars. One of the main characteristics that always being associated with M-type stars is titanium oxide (TiO) molecular spectrum bands. The study has been done to see through different subclasses within the M-type and to observe if there are differences in spectral pattern with each other. Also being observed and analysed is Hα spectral line profile which is to be found at 6562.82 Å as one of the main characteristics of stars. The analysis on Hα spectral profile shows the full width half maximum (FHWM) and equivalent width (EW) for Hα. Also being known from the analysis is the radial velocity of the stars. Several M-type red giant stars were observed from M0 to M6. The data acquisition was done by doing astronomical observation session which had been using 20RC Carbon Truss Ritchey-Chrétien telescope attached to the Paramount-ME Robotic mount, SBIG Self Guided Spectrograph (SGS) with resolution of 1.07 Å per pixel and high resolution Charge-Coupled Device (CCD) camera ST-7E. The IRAF software packages were installed on LINUX interface which was used in data reduction and analysis processes on the collected data. A neon lamp is being used to do the wavelength calibration because of the observable lines of this element are in the higher region of visible wavelength, from 5800 Å to 7500 Å. Briefly, the results show that the dominance of TiO is increasing across the M classs.